A protective sheet for an electronic device and a method of manufacturing and using the same
Patent Information
- Application Number
- CN202610822149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-08
- Publication Date
- 2026-10-27
AI Technical Summary
[0002]随着笔记本电脑的普及与使用场景不断拓展,设备在闭合状态下屏幕与键盘直接接触,长期使用易因摩擦挤压、灰尘异物侵入、油脂残留等问题,导致屏幕划伤、压痕、油污沾染,同时键盘缝隙易堆积碎屑、金属微尘,不仅影响设备外观与清洁度,还会降低操作手感、损害硬件性能,缩短产品使用寿命
1.相比于现有技术,本申请限定天然纤维、聚合物粘结剂、多孔无机材料与磁响应材料的精准配比构建复合纤维基材体系,各组分相互交织粘结形成稳固的三维网状基体结构。其中多孔无机材料凭借高比表面积与多孔通道结构,依靠物理吸附作用高效捕获环境油脂、水汽及细微有机尘粒;核壳结构磁响应材料以磁性无机内核提供磁吸附作用,外层可生物降解聚合物壳层隔绝氧和水汽、防止磁性内核氧化失磁,可定向吸附固定键盘磨损产生的微量磁性金属导电粉尘。本申请实现物理吸附+磁吸附双机制协同除尘,可同时处理有机粉尘、油脂及磁性导电微粒,避免导电粉尘落入键盘缝隙引发接触不良、按键卡滞隐患;同时整体基材及功能填料均采用可生物降解体系,使用废弃后可自然降解,从源头杜绝微塑料残留与化学污染问题,绿色环保性更优。
Smart Images

Figure CN122976163A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of protective accessories for electronic devices, and in particular to a protective sheet for electronic devices, its preparation method, and its application. Background Technology
[0002] With the increasing popularity of laptops and the continuous expansion of their usage scenarios, the screen and keyboard are in direct contact when the device is closed. Long-term use can easily lead to scratches, dents, and oil stains on the screen due to friction, pressure, dust and foreign objects entering, and grease residue. At the same time, debris and metal dust can easily accumulate in the gaps of the keyboard, which not only affects the appearance and cleanliness of the device, but also reduces the feel of operation, damages hardware performance, and shortens the product's lifespan.
[0003] Current laptop screen and keyboard protection products on the market have many shortcomings: traditional cloth cleaning cloths only have basic wiping functions and cannot provide continuous isolation and protection when the device is closed, nor can they be fixed in place to prevent dust from entering gaps; plastic keyboard covers can achieve a certain sealing effect, but they have poor breathability, are prone to static electricity adhesion to the screen and leave permanent indentations, and the materials are not biodegradable, which is not in line with environmental protection trends; some natural fiber protective materials have weak fiber bonding strength, are prone to shedding lint during use, causing secondary pollution, and have limited adsorption capacity for grease, magnetic metal dust, and single function.
[0004] Overall, current protection solutions generally suffer from problems such as functional fragmentation, limited protective effect, easy secondary damage, and insufficient environmental friendliness. They cannot provide physical protection while simultaneously meeting the needs for efficient cleaning and adsorption, adaptive fit, user guidance, and biodegradability throughout the entire life cycle. They are insufficient to meet the current consumer demand for high-quality, multifunctional, and environmentally friendly accessories. Summary of the Invention
[0005] This application provides a protective sheet for electronic devices, a method for preparing the same, and its application, in order to at least solve the above-mentioned technical problems existing in the prior art.
[0006] A first aspect of this application provides a protective sheet for an electronic device, the protective sheet comprising a composite fiber substrate; the composite fiber substrate comprising, by weight percentage, 80% to 90% natural fibers, 8% to 12% polymer binder, and 2% to 8% functional additives; The functional additives include porous inorganic materials and magnetically responsive materials, wherein the porous inorganic materials account for 1% to 6% of the mass of the composite fiber substrate, and the magnetically responsive materials account for 1% to 6% of the mass of the composite fiber substrate. At least one surface of the protective sheet is formed with a biomimetic micro-nano composite structure.
[0007] Specifically, the protective sheet of this application uses natural fibers as the main skeleton, which gives the sheet basic mechanical strength, flexibility and molding stability, so that the sheet has a good feel and structural support, and is not easy to break or shed; the polymer binder, as the adhesive and film-forming component, can effectively combine natural fibers, porous inorganic materials and magnetic response materials into one, forming a continuous and stable structure inside the substrate, improving the integrity and mechanical properties of the composite fiber substrate, and ensuring that the components are evenly distributed and not easy to fall off.
[0008] Porous inorganic materials, with their high specific surface area and porous structure, can strongly adsorb and capillary lock pollutants such as grease, organic dust, and dander, achieving efficient capture and storage of liquid and solid pollutants and preventing pollutant residues on equipment surfaces. Magnetic responsive materials can form uniformly distributed magnetic responsive units within a substrate, directionally attracting, capturing, and fixing magnetic metal dust generated during the use of electronic equipment, preventing metal dust from entering equipment gaps and causing poor contact or internal contamination. The synergistic effect of these two functional components achieves comprehensive cleaning and adsorption of complex pollutants.
[0009] The biomimetic micro-nano composite structure formed on the surface of the protective sheet is composed of multi-level micro-rough structures, which can significantly increase the specific surface area. Through the multi-level micro-structure, it can efficiently capture and store pollutants such as dust and debris of different particle sizes. At the same time, the structure is gentle and will not cause scratch damage to delicate surfaces such as screens and keyboards, thus improving cleaning ability while ensuring safety of use.
[0010] The overall composition and structure work together to enable the protective sheet to achieve efficient physical protection while having a stable ability to adsorb pollutants, thus solving the problems of traditional protective products such as single function, poor cleaning effect, and easy secondary pollution.
[0011] In one embodiment, the composite fiber substrate is integrally formed into a protective sheet using a wet molding process.
[0012] In one embodiment, the natural fiber is selected from plant natural fibers, including at least one of bamboo fiber, hemp fiber, cotton fiber, and wood pulp fiber; the average length of the natural fiber is 1.5~3.5mm and the average aspect ratio is >50.
[0013] Specifically, the aforementioned natural fibers are widely available, easily accessible, and cost-effective, making them suitable for large-scale production and application. Their moderate flexibility and strength provide sufficient structural support for the protective sheet without being too abrasive and scratching the screen, ensuring high safety. They exhibit good hydrophilicity and uniform fiber dispersion, making them suitable for wet molding processes. They can be fully combined with polymer binders and functional additives to form a composite fiber substrate with uniform structure, no agglomeration, and no shedding. Furthermore, the surface of these fibers is rich in active groups, facilitating stable bonding with binders and improving the overall mechanical properties and durability of the substrate. They also exhibit excellent environmental compatibility, are easy to handle after use, and align with the trend of green and environmentally friendly development. The average length of the natural fibers is 1.5~3.5mm. Lengths below 1.5mm result in a dry tensile strength below 2.0kN / m, while lengths above 3.5mm result in a molding uniformity coefficient below 85%. This 1.5~3.5mm range ensures effective interweaving between fibers during wet molding while avoiding insufficient sheet strength or reduced uniformity.
[0014] In one embodiment, the polymer binder is selected from at least one of waterborne acrylic resin, waterborne polyurethane resin, waterborne polyvinyl alcohol, carboxymethyl cellulose, and chitosan.
[0015] Specifically, the above-mentioned polymer binders (1) are all water-based systems, which can be uniformly dispersed in water with natural fibers, porous inorganic materials, and magnetically responsive materials. The slurry has good compatibility, does not agglomerate, and does not separate during molding. (2) They can coat the surface of natural fibers and fill the gaps between fibers, firmly bonding the fiber gaps, inorganic powders, and magnetically responsive particles into a whole, greatly improving the dry / wet strength of the sheet, and preventing powder and lint shedding. (3) In particular, self-crosslinking acrylic resins and water-based polyurethanes can form hydrogen bonds or even chemical bonds with the hydroxyl groups on the surface of natural fibers after drying and curing, constructing a stable three-dimensional network. The sheet is resistant to bending and repeated opening and closing. (4) The surface of the film is delicate and soft after film formation, and no hard particles are generated, avoiding scratching electronic devices. (5) The surface of the film is rich in functional groups after film formation, which is conducive to the subsequent preparation of biomimetic micro-nano composite structures.
[0016] In a preferred embodiment, the polymer binder is selected from self-crosslinked acrylic resin. During the drying and curing stage of the wet molding process, when the temperature reaches the set crosslinking temperature, such as 85°C, the carboxyl groups carried on the resin molecular chain and the hydroxyl groups on the surface of the natural fiber undergo an esterification reaction under the catalysis of a catalyst such as ammonium zirconium carbonate, generating ester bonds. This reaction forms strong covalent bond bridges at the fiber-to-fiber contact points and at the interface between the fiber and functional additives, thereby constructing a three-dimensional network structure within the material. This chemical crosslinking network greatly enhances the mechanical strength of the sheet in both dry and wet states, fundamentally overcoming the defects of poor mechanical strength and easy shedding of high-porosity fiber materials. Furthermore, since the ester bonds can be hydrolyzed by enzymes secreted by microorganisms in the natural environment, the overall biodegradability of the material is not affected.
[0017] In one embodiment, the porous inorganic material is selected from at least one of mesoporous silica, zeolite molecular sieve, and magnesia.
[0018] Specifically, the reasons for choosing the above three materials are as follows: (1) All three have rich microporous / mesoporous channel structures, large specific surface area, and high porosity. They can efficiently adsorb human oil, sweat stains, dust particles, dander, and organic volatiles on the surface of electronic devices by relying on extremely strong physical adsorption. Relying on the capillary coagulation effect of the channels, liquid oil is firmly locked inside the channels, making it difficult for it to be released and contaminated on the surface of the equipment again. (2) All three types of materials are inorganic inert mineral materials with stable chemical properties. They do not oxidize, yellow, or release harmful substances. They will not corrode or scratch the screen coating, paint, and plastic shell of electronic devices, and are suitable for the protection of precision electronic devices. (3) The particle size of the powder can be adjusted. It can be uniformly mixed and dispersed with natural fibers and polymer binders during wet pulping. There is no agglomeration or sedimentation. After molding, it is evenly distributed inside the sheet, and the overall adsorption performance is consistent. (4) Excellent hydrophilic wetting properties, can be stably dispersed directly in aqueous slurry without floating powder or settling, and has excellent compatibility with fiber slurry. It does not affect the papermaking, pressing, drying and curing film-forming process, and is suitable for large-scale wet preparation. (5) Compared with hard fillers such as quartz powder and kaolin, these three materials have soft particle morphology and moderate hardness. After being embedded in the fiber matrix, they will not be exposed to form sharp hard points. There is no risk of scratching when they are in contact with the screen for long-term wiping and isolation protection. (6) The pore size of mesoporous silica and zeolite molecular sieve is regular and adjustable. They have selective adsorption capacity for oil molecules and small organic molecules. Magnesia silicate itself has a layered adsorption structure and has a natural affinity for adsorption of acute stains and oil stains. The three can be used alone or in combination to complement each other, taking into account the simultaneous capture of large molecular oil stains and fine dust.
[0019] Specifically, in the composite fiber substrate, approximately 40% of the porous inorganic material is mechanically trapped and embedded in the pores of the fiber network, approximately 35% is attached to the fiber surface (bound by hydrogen bonds and van der Waals forces), and approximately 25% is encapsulated by the polymer binder. No covalent chemical cross-linking occurs between the porous inorganic material and the fiber; however, the silanol groups (-SiOH) or aluminum hydroxyl groups (-AlOH) on its surface can form hydrogen bonds with the carboxyl groups of the carboxyl-COOH-containing polymer binder. During the drying and curing stage, partial dehydration condensation forms Si-OC or Al-OC bonds, thereby enhancing interfacial adhesion and reducing powder shedding. Simultaneously, the porous structure creates an anchoring effect through the physical adsorption of the polymer binder, further improving the fixation stability of the additive.
[0020] In a preferred embodiment, the porous inorganic material is selected from mesoporous silica, which has a regular array of nanoscale pores with a pore size distribution between 2 and 50 nm. This special pore structure produces a significant capillary coagulation effect: when the sheet comes into contact with the surface of an electronic device contaminated with grease, grease molecules are drawn into the nanopores under the action of surface tension. Due to the extremely small pore diameter, the liquid forms a concave liquid surface within the pores, generating an additional pressure difference, thereby continuously drawing in and firmly locking the liquid grease molecules inside the pores. Meanwhile, the mesoporous silica has a diameter of 500-1000 nm. 2 The specific surface area of / g ensures that it can generate sufficient van der Waals forces with pollutant molecules, thus achieving efficient physical adsorption of organic pollutants.
[0021] In one embodiment, the magnetically responsive material includes a magnetic inorganic core and a polymer shell covering the surface of the magnetic inorganic core, wherein the mass ratio of the magnetic inorganic core to the polymer shell is 1:0.2~0.6.
[0022] Specifically, the material of the magnetic inorganic core is selected from at least one of iron(II,III) oxide (Fe3O4), γ-Fe2O3, manganese ferrite (MnFe2O4), and nickel ferrite (NiFe2O4).
[0023] All of the above materials have the characteristics of rapid magnetization under an applied magnetic field and zero residual magnetism after the magnetic field is removed, which enables the directional capture of magnetic metal dust without producing permanent magnetic interference.
[0024] Specifically, the polymer shell is a biodegradable polymer selected from at least one of polylactic acid and chitosan; the thickness of the polymer shell is 5~50 nm.
[0025] The key function of this polymer shell is to isolate the magnetic inorganic core from water vapor and oxygen in the environment through steric hindrance, thus preventing it from oxidizing and rusting and losing its magnetic function.
[0026] Specifically, a mass ratio range of 1:0.2~0.6 can ensure that the polymer shell completely covers the magnetic inorganic core, effectively isolates water vapor and oxygen to prevent oxidation and demagnetization, maintains a suitable magnetic content of the magnetic response material, ensures the construction of a stable weak magnetic field network in the composite fiber substrate, and avoids the shell ratio being too high, which would affect the mechanical and air permeability properties of the sheet.
[0027] Specifically, when the protective sheet covers an electronic device, the uniformly distributed magnetic response material forms a weak magnetic field network at the microscopic level. Although the magnetic field strength is insufficient to affect the hardware of the electronic device, it is sufficient to attract scattered magnetic metal particles, capture and fix them, and effectively avoid the risk of poor circuit contact that may be caused by these conductive dust particles falling into the gaps of electronic devices (such as keyboard gaps).
[0028] In one embodiment, the composite fiber substrate further includes 1% to 3% of the total mass of the composite fiber substrate, which is a bio-based elastic fiber with shape memory effect; the bio-based elastic fiber is selected from at least one of polycaprolactone fiber and bio-based polyurethane fiber.
[0029] Specifically, a specific amount of bio-based elastic fibers with shape memory effect are incorporated into the composite fiber substrate. The glass transition temperature of these fibers is adapted to the temperature range of the electronic device surface during normal operation. These fibers achieve their function through the thermal motion characteristics of polymer molecular chain segments: when the ambient temperature is below the glass transition temperature, the molecular chain segments are frozen, and the fiber as a whole exhibits rigidity, maintaining the protective sheet's own shaped structure and supporting strength; when the electronic device generates heat during operation, and the surface temperature rises above the fiber's glass transition temperature, the molecular chain segments are activated and gain mobility, and the fiber transitions from a glassy state to a highly elastic state. Macroscopically, this manifests as a softening of the material and a decrease in modulus, significantly improving the overall flexibility of the protective sheet. Utilizing this temperature-dependent dynamic stiffness and reversible flexibility adjustment characteristic, the sheet can adaptively conform to the curved surface of the electronic device screen and the concave and convex shapes between buttons. It achieves a tight interface fit when the device is closed, and smoothly adapts to deformation and separates stably during opening and closing, effectively optimizing the contact fit between the protective sheet and the device surface, balancing structural stabilization and adaptive interface fit.
[0030] In one embodiment, the biomimetic micro-nano composite structure is composed of micron-scale fibrous protrusions and nano-scale filament networks interwoven together.
[0031] In one embodiment, the biomimetic micro-nano composite structure is formed by etching at least one surface of a protective sheet using either plasma treatment or bio-enzymatic hydrolysis.
[0032] In a preferred embodiment, the biomimetic micro / nano composite structure is formed by plasma etching of at least one surface of a protective sheet.
[0033] Specifically, the process is carried out in a mixed atmosphere of oxygen and argon. The reactive oxygen species and argon ions in the high-energy plasma preferentially bombard and etch the amorphous regions on the fiber surface, while the more crystalline regions are preserved. This selective etching results in the formation of numerous nanoscale filament protrusions on the micron-sized fiber backbone, creating a multi-level rough structure. This multi-scale structure traps contaminants through multiple physical mechanisms: the micron-sized protrusions mechanically intercept larger particles, while the nanoscale filaments adsorb ultrafine particles through extremely strong van der Waals forces. Its enormous specific surface area also provides an ideal substrate for subsequent functional coatings.
[0034] In one embodiment, the surface of the biomimetic micro / nano composite structure is further loaded with an oleophilic-hydrophobic coating, the material of which is selected from at least one of modified cellulose derivatives and rosin derivatives.
[0035] Specifically, a biodegradable oleophilic and hydrophobic coating, such as cellulose acetate, is loaded onto the surface of the biomimetic micro-nano composite structure. The cellulose acetate molecular chain is rich in acetyl nonpolar groups, exhibiting good similarity and compatibility with the hydrocarbon molecular structure of greases, thus endowing the coating with excellent oleophilic adsorption properties. When grease stains on the surface of electronic devices come into contact with the functional surface of the sheet, the coating promotes rapid grease spreading and penetrating into the pores of the biomimetic micro-nano composite structure, where it is locked and stored. Simultaneously, the coating possesses extremely low surface energy, synergistically constructing a stable Cassie-Baxter solid-gas composite interface with the micro-nano multi-level rough structure, significantly increasing the water droplet contact angle and effectively inhibiting water wetting and penetration. This coating forms a functional synergistic system with the biomimetic micro-nano composite structure, endowing the sheet with selective wetting properties. It can preferentially and directionally adsorb and capture liquid grease and organic stains, while blocking water vapor and water stains from penetrating and remaining. This enhances the sheet's oil stain cleaning and adsorption capabilities while preventing water vapor from entering the electronic device and causing moisture and corrosion risks.
[0036] In one embodiment, a biomimetic micro-nano composite structure is formed on one surface of the protective sheet; the other surface is provided with an information-carrying surface for carrying customized graphic and textual information about the operation of electronic devices.
[0037] Specifically, the information-carrying surface is treated with a transparent pre-coating liquid to form a smooth base, and customized graphic information is printed using water-based ink.
[0038] Specifically, if one side of the protective sheet needs to be set as an information-carrying surface, then there is no need to construct a biomimetic micro-nano composite structure on that side. Instead, the other side is constructed as a functional surface and forms an exposed biomimetic micro-nano composite structure, ensuring that its multi-level rough morphology and pore structure are completely preserved, so as to give full play to the capture and adsorption of various pollutants. The information-carrying surface is made by printing graphics on the original flat surface of the substrate after pre-coating and leveling, so as to avoid the micro-nano structure being filled and blocked and losing its function, while simplifying the process and reducing production costs.
[0039] Specifically, the transparent pre-coating liquid is selected from at least one of waterborne polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl methyl cellulose, chitosan, modified starch, and waterborne bio-based polyurethane.
[0040] The aforementioned pre-coating liquids form uniform films with high transparency, do not obscure the printed images underneath, and do not yellow or show through the base color. They can penetrate the pores of natural fiber surfaces, fill in uneven textures, form a smooth and dense printing substrate, and improve ink adhesion. They have excellent compatibility with composite fiber substrates, form films at room temperature, and do not require harsh high-temperature conditions. They can form hydrogen bonds with fiber surfaces, resulting in strong coating adhesion that is not prone to peeling or flaking. All are environmentally friendly bio-based / natural polymer materials, matched with an overall biodegradable design, and are solvent-free and low in volatile organic compounds (VOCs). They have moderate surface tension, are compatible with environmentally friendly water-based inks, and produce clear, non-smudged, and well-adhesive printed images.
[0041] Specifically, the aforementioned transparent pre-coating liquid can penetrate into the fiber gaps, forming a continuous, dense, smooth film on the substrate surface after drying. By filling the pores inside and on the surface of the fibers, it effectively reduces the ink absorption capacity of the composite fiber substrate, preventing excessive penetration and diffusion of environmentally friendly water-based inks into the fiber pores during subsequent printing, ensuring sharp edges and clear, regular patterns in the printed graphics. On the smooth substrate formed by the pre-coating liquid, environmentally friendly water-based ultraviolet (UV) curing inks, combined with digital printing technology, can accurately print customized guidance information such as shortcut key icons and touch operation gestures for electronic devices onto the information-carrying surface. This achieves excellent printability and image adhesion thanks to the smooth film layer, while also providing intuitive equipment operation instructions, offering users convenient and intuitive real-time operation guidance. Furthermore, the overall material formulation is environmentally friendly and non-toxic, aligning with the biodegradable green design concept.
[0042] In one embodiment, the surface of the information-carrying surface is further covered with a transparent protective film to protect the customized graphic information on the information-carrying surface from contamination and wear; the transparent protective film is made of microbially synthesized polyester material.
[0043] Specifically, microbially synthesized polyester materials include, but are not limited to, polyhydroxyalkanoates (PHA), polyhydroxybutyrate (PHB), and polyhydroxybutyrate-valerate copolyester (PHBV).
[0044] Specifically, this peelable transparent protective film combines with the information-carrying surface using a pressure-sensitive adhesive with weak adhesion properties, precisely controlling the interface adhesion force within the range of 0.1~0.5N / 25mm. This protective film effectively protects the printed graphic layer during product transportation, storage, and handling, preventing damage from external friction, scratches, dust, and contamination. Furthermore, the precise design of the adhesion force ensures a firm bond that prevents self-detachment, while allowing end-users to easily and completely peel off the film without damaging the printed graphic surface. This structural and parameter adaptation design ensures that the printed graphics are intact and clear upon delivery, maintaining the product's information transmission function, effectively optimizing the product's unboxing appearance, enhancing the initial user experience, and increasing its added value. Simultaneously, the microbially synthesized polyester material is both environmentally friendly and biodegradable, aligning with the overall green and biodegradable design concept.
[0045] A second aspect of this application provides a method for preparing the aforementioned protective sheet, comprising the following steps: S1: A mixture is prepared by mixing natural fibers, polymer binders, porous inorganic materials and magnetically responsive materials according to mass percentages; S2: The mixture is molded and dried to obtain a composite fiber substrate; S3: At least one surface of the composite fiber substrate is etched to form a biomimetic micro-nano composite structure, thereby producing a protective sheet.
[0046] In one embodiment, before mixing, step S1 further includes a step of preparing a magnetically responsive material, specifically including: preparing a magnetic inorganic material as a core; forming a polymer shell on the surface of the magnetic inorganic material by means of polymer coating and / or direct coating, thereby obtaining the magnetically responsive material.
[0047] Specifically, the steps for preparing magnetic inorganic materials include: mixing divalent and trivalent metal salts of the corresponding magnetic inorganic materials, adding an alkaline precipitant dropwise under inert gas and stirring conditions, adjusting the pH of the reaction system to 9-11 to carry out a co-precipitation reaction, and obtaining the magnetic inorganic material.
[0048] More specifically, the molar ratio of the divalent metal salt to the trivalent metal salt is 1:1.8~2.2.
[0049] More specifically, the inert gas is selected from at least one of argon and nitrogen.
[0050] More specifically, the temperature of the mixed solution is raised to 60-80°C before adding the alkaline precipitant.
[0051] More specifically, the alkaline precipitant is selected from at least one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate.
[0052] More specifically, after the addition is complete, continue stirring for 30-60 minutes to obtain magnetic inorganic materials with a particle size of 8-15 nm.
[0053] Specifically, the polymer coating includes: using a magnetic inorganic material as a substrate, under the action of a catalyst, causing lactic acid monomers to undergo a ring-opening polymerization reaction on the surface of the magnetic inorganic material, thereby forming a dense polylactic acid shell on the surface of the magnetic inorganic material.
[0054] More specifically, the catalyst is selected from at least one of stannous octoate, stannous chloride, zinc oxide, zinc lactate, and zinc stearate.
[0055] Specifically, direct coating includes directly coating the surface of magnetic inorganic materials with chitosan.
[0056] Specifically, the mass ratio of the magnetic inorganic material to the polymer shell is 1:0.2~0.6.
[0057] In one embodiment, step S1 involves mixing natural fibers, polymer binders, porous inorganic materials, magnetically responsive materials, and bio-based elastic fibers with shape memory effect by mass percentage to obtain a mixture.
[0058] In one embodiment, the concentration of the mixture in step S1 is 0.6% to 1.0%.
[0059] Specifically, too low a concentration will result in excessively sparse fiber dispersion, poor molding uniformity, and unstable quantitative distribution; too high a concentration will lead to excessively high slurry viscosity, causing porous inorganic materials and magnetically responsive materials to easily agglomerate, resulting in uneven dispersion and affecting the pore structure and magnetic response uniformity of the sheet. Using the above-mentioned concentration range can balance fiber dispersibility, filler dispersion uniformity, and the consistency of the microstructure of the wet-formed preform.
[0060] In one embodiment, step S2 is performed using a wet molding process; step S2, molding and drying, specifically includes the following steps: dehydrating and molding the mixture under a vacuum of -0.06 to -0.04 MPa to obtain a quantity of 60 to 70 g / m³. 2 The wet paper sheet is pressed by a press roller and then subjected to gradient drying to obtain a composite fiber substrate.
[0061] Specifically, the wet paper sheet is pressed sequentially by two sets of press rollers, with the linear pressure of the two sets of press rollers controlled at 30~40kN / m and 45~55kN / m, respectively.
[0062] Specifically, the gradient drying process includes: drying at 75~85℃ for 1.5~2.5 min; drying at 100~110℃ for 2.5~3.5 min; and drying at 85~95℃ for 2.0~2.5 min.
[0063] The first stage of drying is preliminary dehydration and drying; the second stage of drying is to promote the cross-linking reaction of the polymer binder; and the third stage of drying completes the curing and shaping of the composite fiber substrate.
[0064] In one embodiment, the etching process in step S3 includes either plasma etching or bio-enzymatic etching.
[0065] Specifically, the conditions for plasma etching include: a mixed atmosphere of oxygen and argon with a volume ratio of 1:2 to 3, a vacuum level controlled at 15 to 30 Pa, a discharge power of 80 to 150 W, and a processing time of 2 to 6 min.
[0066] Plasma etching can selectively etch amorphous regions on fiber surfaces while preserving crystalline morphology, enabling the rapid construction of micro / nano-level rough structures.
[0067] Specifically, the conditions for bio-enzymatic etching include: using a cellulase aqueous solution with a mass concentration of 0.5%~2.0% for immersion, a treatment temperature of 45~60℃, a pH value of 4.5~6.0, and an immersion time of 15~40 min.
[0068] Bio-enzymatic etching can gently degrade amorphous cellulose on the fiber surface, naturally forming a network of uneven filaments without compromising the overall mechanical strength of the substrate.
[0069] In one embodiment, after forming the biomimetic micro-nano composite structure, step S3 further includes: loading an oleophilic and hydrophobic coating onto the surface of the biomimetic micro-nano composite structure, wherein the loading method is selected from either immersion or spraying, and the drying temperature after loading is 60~70°C.
[0070] In one embodiment, after forming a biomimetic micro-nano composite structure on one surface of the composite fiber substrate in step S3, an information carrying surface is set on the other surface of the composite fiber substrate; the method for setting the information carrying surface includes: coating a transparent pre-coating liquid on the other surface of the composite fiber substrate, drying it at 60~80°C to form a printing base, and printing water-based ink on the surface of the printing base to form customized graphic information.
[0071] Specifically, the coating amount and printing parameters are set according to specific needs, and no specific restrictions are imposed here.
[0072] Specifically, after setting the information carrying surface, the method further includes: laminating a transparent protective film onto the surface of the information carrying surface, which is bonded to the information carrying surface by pressure-sensitive adhesive; the lamination temperature is 70~80℃ and the pressure is 0.2~0.4MPa.
[0073] More specifically, the thickness of the transparent protective film is 10~15μm.
[0074] More specifically, the amount of pressure-sensitive adhesive applied depends on the actual needs and is not limited here.
[0075] A third aspect of this application provides the application of the aforementioned protective sheet in surface protection of any one of the following: external keyboards for laptops, desktop computers, and tablet keyboards.
[0076] Specifically, the protective sheet is applied to the surface of the key area of the keyboard.
[0077] This application has at least the following beneficial effects: 1. Compared to existing technologies, this application specifies a precise ratio of natural fibers, polymer binders, porous inorganic materials, and magnetically responsive materials to construct a composite fiber substrate system. The components interweave and bond to form a stable three-dimensional network matrix structure. The porous inorganic materials, with their high specific surface area and porous channel structure, efficiently capture environmental grease, moisture, and fine organic dust particles through physical adsorption. The core-shell structured magnetically responsive material provides magnetic adsorption with its magnetic inorganic core, while the outer biodegradable polymer shell isolates oxygen and moisture, preventing oxidation and demagnetization of the magnetic core. It can also directionally adsorb and fix trace amounts of magnetic conductive dust generated by keyboard wear. This application achieves synergistic dust removal through a dual mechanism of physical adsorption and magnetic adsorption, simultaneously handling organic dust, grease, and magnetically conductive particles. This prevents conductive dust from falling into keyboard gaps and causing poor contact or key jamming. Furthermore, the entire substrate and functional fillers are biodegradable, allowing for natural degradation after use, eliminating microplastic residues and chemical pollution at the source, resulting in superior environmental friendliness.
[0078] 2. Compared to existing technologies, this application incorporates bio-based elastic fibers with shape memory effect into a composite fiber substrate and etches its surface to construct a biomimetic micro / nano composite structure interwoven with micron-scale fiber protrusions and a nano-scale filament network. The doped bio-based elastic fibers with shape memory effect can adapt their softness and shape to the slight heat generated during the operation of electronic devices, thus closely conforming to the curved contours of the screen and keyboard, ensuring a tight fit when the device is closed and smooth opening and closing without jamming. At the same time, the micron-scale protrusions and nano-scale fiber network formed on the surface create a huge specific surface area and complex capillary channels, which can mechanically intercept and adhere to dust particles of different sizes, further enhancing the dustproof barrier effect; simultaneously, the biomimetic micro / nano composite structure, combined with the subsequent oleophilic and hydrophobic coating, constructs a stable composite interface, giving the sheet excellent hydrophobic, anti-fouling, and self-cleaning properties, preventing sweat, water stains, and oil stains from penetrating into the keyboard, reducing corrosion and stain residue. In addition, the use of wet molding, gradient pressing and three-stage temperature-controlled drying processes allows the polymer binder to fully cross-link and cure, significantly improving the homogeneity, mechanical strength and dimensional stability of the sheet structure, making it less prone to deformation and fuzzing, and suitable for long-term repeated bonding applications.
[0079] 3. Compared to existing technologies, this application features an information-carrying surface on the unstructured side of the sheet, using a transparent pre-coated liquid to seal the fiber gaps, effectively inhibiting ink bleed and ensuring clear and durable operation guidance graphics. Environmentally friendly water-based inks are used to print shortcut keys, touch gestures, and other markings, providing both protection and operation guidance. A peelable transparent protective film is laminated onto the printed surface, protecting it from scratches and stains during storage, transportation, and pre-sales, while also allowing for complete manual peeling. The biomimetic structure of the functional surface, combined with an oleophilic and hydrophobic coating, preferentially adsorbs and locks in liquid grease while blocking moisture penetration. This integrates physical isolation protection, multi-functional dust and dirt removal, operation information carrying, peelable protection, and easy cleaning into a single sheet, achieving a high degree of multi-functional integration and significantly improving usability and user experience.
[0080] It should be understood that the description in this section is not intended to identify key or essential features of the embodiments of this application, nor is it intended to limit the scope of this application. Other features of this application will become readily apparent from the following description. Attached Figure Description
[0081] The above and other objects, features, and advantages of exemplary embodiments of this application will become readily apparent from the following detailed description taken in conjunction with the accompanying drawings. Several embodiments of this application are illustrated in the drawings by way of example and not limitation, wherein: In the accompanying drawings, the same or corresponding reference numerals indicate the same or corresponding parts.
[0082] Figure 1 A schematic diagram of the process for preparing the protective sheet for a laptop computer according to Embodiment 1 of this application is shown. Detailed Implementation
[0083] To make the objectives, features, and advantages of this application more apparent and understandable, the technical solutions in the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0084] Example 1 This embodiment describes the preparation of a protective sheet for a laptop computer. The preparation process is described in [link to documentation]. Figure 1 The details are as follows: (1) FeCl2 and FeCl3 salts were dissolved in deoxygenated and deionized water at a molar ratio of 1:2. The temperature was raised to 70°C under the protection of argon. Ammonia water was added dropwise while stirring vigorously. The pH value of the reaction system was controlled to be 10±0.5 to carry out the co-precipitation reaction. After the addition was completed, stirring was continued for 45 min to obtain a magnetic material with a particle size of 15 nm.
[0085] Using magnetite as a substrate, lactic acid monomers undergo ring-opening polymerization on the surface of the magnetite under the action of stannous octoate, thereby forming a dense polylactic acid shell with a thickness of approximately 25 nm on the surface of the magnetite. This yields the magnetically responsive material polylactic acid-coated magnetite. The mass ratio of magnetite to polylactic acid shell is 1:0.4.
[0086] (2) Based on the total weight of solids, take 83% bamboo fiber (average length 2.2 mm, average aspect ratio 80), 8% self-crosslinking acrylic resin solids (provided by an emulsion with a solid content of 45%, the amount of emulsion added is 8%÷45%≈17.8%), and 5% mesoporous silica (specific surface area 800 m²). 2 The mixture consists of 2% polylactic acid-coated magnetite (core-shell structure, with an average particle size of 15nm and a shell thickness of 25nm) and 2% polycaprolactone fiber, mixed uniformly in a pulper at a slurry concentration of 0.8%.
[0087] (3) The mixed slurry from step (2) is fed to an inclined screen forming machine and dehydrated and formed under a vacuum of -0.05 MPa to form a mass of 65 g / m 2 The wet paper sheet is pressed sequentially by two sets of press rollers at linear pressures of 35 kN / m and 50 kN / m, respectively, and then enters the drying cylinder for drying. During the drying process, three temperature zones are set: the first zone is 80℃ for 2 minutes for preliminary drying; the second zone is 105℃ for 3 minutes to allow the resin to undergo a cross-linking reaction; and the third zone is 90℃ for 2 minutes to complete the curing and shaping of the composite fiber substrate, at which point the composite fiber substrate is obtained.
[0088] (4) The composite fiber substrate obtained in step (3) is subjected to plasma treatment equipment in a mixed gas with an oxygen to argon volume ratio of 1:3, with the vacuum degree controlled at 20 Pa, and a discharge power of 150 W for 120 s to form a biomimetic micro-nano composite structure on one surface of the composite fiber substrate. Then, it is passed through an impregnation tank with a concentration of 2% cellulose acetate solution at a speed of 3 m / min and dried at 65 °C to form an oleophilic and hydrophobic coating.
[0089] (5) Apply 8 g / m to another surface of the composite fiber substrate2 A hydroxypropyl methylcellulose pre-coating solution was applied and dried with hot air at 70°C to form a printing substrate. Using environmentally friendly water-based UV inks, the user manual for a laptop was printed at a resolution of 600 dpi using an inkjet printer. The UV curing energy was 120 mJ / cm². 2 At this point, an information-carrying surface is formed on the other surface of the composite fiber substrate.
[0090] (6) Finally, a 12μm thick polyhydroxyalkanoate protective film is laminated onto the surface of the information-carrying surface. This protective film is bonded to the information-carrying surface using pressure-sensitive adhesive, with a coating amount of 3.5g / m. 2 The lamination temperature is 75℃ and the pressure is 0.3MPa. This completes the preparation of the protective sheet for the laptop computer.
[0091] The protective sheet prepared using the above process is used as a built-in accessory for laptops, and its specific application process is as follows: On the laptop packaging line, the operator lays the protective sheet flat on the keyboard area, with its functional surface (the side treated with plasma etching and oleophilic and hydrophobic coating) facing the screen and the information-carrying surface (the side covered with a peelable protective film) adhering to the surface of the keyboard keys. The micro-texture structure of the protective sheet itself forms static friction limit with the keyboard surface, so that the sheet is stable on the keyboard without shifting or slipping.
[0092] After the laptop lid is closed, the sheet material is evenly pressed between the screen and the keyboard. During this process, the biomimetic micro-nano composite structure of the functional surface adheres to the initial contaminants on the screen surface through capillary action and van der Waals forces; the oleophilic and hydrophobic coating selectively adsorbs organic contaminants such as precipitated silicone oil; and at the same time, the magnetically responsive material continuously captures metal wear particles generated by vibration.
[0093] When the ambient temperature (operating temperature) reaches about 35℃, the bio-based elastic fibers with shape memory effect in the sheet undergo a phase change, and the modulus decreases from 1200MPa to 25MPa, which increases the softness of the sheet and automatically adapts to the curvature of the screen and the concavity and convexity of the keyboard, ensuring uniform interface contact.
[0094] After unpacking, the end user should first remove the protective sheet, and then peel off the protective film at a peel angle of less than 30°. At this point, the surface gloss of the printed layer remains above 65 GU, and the clarity of the graphics and text is intact.
[0095] After completing the computer initialization setup by referring to the printed instructions, the user can continue to place the sheet on the keyboard for use. During daily use, the sheet will continuously absorb newly generated skin flakes, dust, and grease.
[0096] Example 2 This embodiment prepares a protective sheet for a laptop computer. The difference from Embodiment 1 is that the protective sheet in this embodiment does not contain bio-based elastic fibers with shape memory effect, i.e., it does not contain polycaprolactone fibers.
[0097] Step (2) involves taking 85% bamboo fiber, 8% self-crosslinking acrylic resin solids, 5% mesoporous silica, and 2% polylactic acid-coated iron oxide magnetic material by total solid weight, and mixing them evenly in a pulper at a slurry concentration of 0.8%. The rest is the same as in Example 1, and will not be repeated here.
[0098] Comparative Example 1 This comparative example provides a protective sheet for a laptop computer, which is a commercially available non-woven keyboard cleaning cloth (the main material is polyester fiber).
[0099] Comparative Example 2 This comparative example prepared a protective sheet for a laptop computer. The difference from Example 1 is that the protective sheet of this comparative example did not contain any magnetically responsive material, that is, it did not contain polylactic acid-coated iron oxide magnetic material.
[0100] Step (2) involves taking 85% bamboo fiber, 8% self-crosslinking acrylic resin solids, 5% mesoporous silica, and 2% polycaprolactone fiber by total solid weight, and mixing them evenly in a pulper at a pulping concentration of 0.8%. The rest is the same as in Example 1, and will not be repeated here.
[0101] Comparative Example 3 This comparative example prepares a protective sheet for a laptop computer. The difference between this comparative example and Example 1 is that the protective sheet in this comparative example does not have a biomimetic micro-nano composite structure (no plasma treatment), that is, it does not have step (4). The rest is the same as in Example 1, and will not be repeated here.
[0102] Comparative Example 4 This comparative example prepared a protective sheet for a laptop computer. The difference from Example 1 is that starch was used in this comparative example instead of the self-crosslinking acrylic resin in Example 1. The rest is the same as in Example 1, and will not be repeated here.
[0103] Test case The grease adsorption rate, metal dust capture rate, 60-day biodegradation rate, shedding amount, and dry tensile strength of the protective sheets of Examples 1-2 and Comparative Examples 1-4 were tested.
[0104] 1. Oil Adsorption Rate Test Method: A standard simulated keyboard oil stain system was used. Edible vegetable oil was selected to prepare simulated oil stains, which were evenly coated on the surface of the standard keyboard simulated sample and the initial mass of the oil stains was recorded. The same size sheet sample was flatly covered on the surface of the oil stains. After standing at room temperature for 24 hours for adsorption, the sheet was removed and the mass difference of the sample before and after adsorption was weighed. The oil adsorption rate was calculated as follows: Oil adsorption rate = (mass of oil adsorbed by the sample / total mass of the initial oil stains) × 100%.
[0105] 2. Metal Dust Capture Rate Test Method: Common magnetic iron-based metal dust particles from keyboard wear were selected, sieved to obtain powder with a uniform particle size range, and evenly sprinkled into the simulated groove area of a standard keyboard. The test sheet was laid flat to cover the particles, left to stand for 24 hours, and then the sheet was removed. The unadsorbed residual metal dust was collected and weighed. Metal dust capture rate = (mass of initial metal dust - mass of residual dust) / mass of initial metal dust × 100%.
[0106] 3.60-day biodegradation rate test method: According to GB / T 19277 compost biodegradation test standard, the sheet to be tested is made into a standard sample and placed in a controlled constant temperature and humidity composting environment for continuous composting degradation in the dark for 60 days; the residual dry weight of the sample before and after degradation is tested respectively, and the biodegradation rate is calculated: Biodegradation rate = (initial dry weight of sample - residual dry weight after degradation) / initial dry weight of sample × 100%.
[0107] 4. Test method for chip loss: Cut the sheet to be tested into samples of uniform specifications, fix them on the fixture of the abrasion testing machine, set a constant friction stroke and number of friction cycles, and conduct a reciprocating friction test with a standard dust-free friction surface; after the test, collect the sample surface and the fallen debris, and weigh the total chip loss mass using a precision analytical balance.
[0108] 5. Dry tensile strength test method: According to GB / T 12914 paper and paperboard tensile strength test standard, the sheet to be tested is cut into standard strip specimens, and after equilibration in a constant temperature and humidity drying environment, a dry tensile test is performed using an electronic tensile strength tester. The tensile strength at the time of specimen breakage is recorded, and the unit is kN / m.
[0109] The test results are shown in Table 1.
[0110] Table 1
[0111] Table 1 shows that the biomimetic micro-nano composite structure is the core enhancing factor for oil adsorption. In Comparative Example 3, which removes this structure, the adsorption rate drops sharply from 96.4% to 65.8%, proving that the synergistic effect of the multi-level rough structure and porous filler significantly improves the physical interception and adsorption capacity of oil.
[0112] Regarding the metal dust capture rate, Examples 1, 2, and 3 are all close to 100%, while Comparative Example 1 is 0% and Comparative Example 2 is only 11.4%. This indicates that the magnetic component is the decisive factor in capturing metal dust, while the shape memory effect of bio-based elastic fibers, biomimetic micro / nano composite structures, and binder type have almost no impact on this performance. The magnetically responsive material of this application can form a stable weak magnetic field network, effectively fixing conductive metal dust generated by keyboard wear.
[0113] Regarding the 60-day biodegradation rate, Examples 1, 2, 2, 3, and 4 all exceeded 87.5%, while the commercially available Comparative Example 1 only achieved 3.5%. This indicates that the fully biodegradable system of this application can achieve efficient degradation in a composting environment, far superior to non-degradable polyester nonwoven fabrics. Furthermore, the presence of bio-based elastic fibers with shape memory effect, biomimetic structures, and magnetic components does not affect the overall biodegradability of the material.
[0114] Regarding the amount of lint, Examples 1, 2, 2, and 3 showed extremely low lint levels, while Comparative Examples 1 and 4 showed severe lint shedding. This indicates that self-crosslinking acrylic resin is the key to maintaining the stability of the substrate structure and reducing lint shedding: after replacing it with starch, the lint shedding increased to 12.8 mg, proving that the self-crosslinking resin can form a strong bonding network in the fiber bonds, avoiding powder and lint shedding during use. Bio-based elastic fibers with shape memory effect and biomimetic structures have a relatively small impact on the amount of lint shedding.
[0115] Regarding dry tensile strength, the strengths of Examples 1, 2, 2, and 3 were significantly higher than those of Comparative Example 1 and 4. This indicates that the synergistic effect of the self-crosslinking resin, natural fibers, and functional fillers significantly improved the mechanical strength of the substrate; the starch binder could not provide sufficient crosslinking force, leading to easy tearing and breakage of the sheets. Magnetic components, bio-based elastic fibers with shape memory effect, and biomimetic structures had limited impact on the strength of the substrate.
[0116] It should be understood that the various forms of processes shown above can be used to rearrange, add, or delete steps. For example, the steps described in this application can be executed in parallel, sequentially, or in different orders, as long as the desired result of the technical solution of this application can be achieved, and this is not limited herein.
[0117] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "a plurality of" means two or more, unless otherwise explicitly specified.
[0118] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A protective sheet for electronic devices, characterized in that, The protective sheet comprises a composite fiber substrate; by weight percentage, the composite fiber substrate comprises 80% to 90% natural fibers, 8% to 12% polymer binder, and 2% to 8% functional additives. The functional additives include porous inorganic materials and magnetically responsive materials, wherein the porous inorganic materials account for 1% to 6% of the mass percentage of the composite fiber substrate, and the magnetically responsive materials account for 1% to 6% of the mass percentage of the composite fiber substrate. At least one surface of the protective sheet is formed with a biomimetic micro-nano composite structure.
2. The protective sheet according to claim 1, characterized in that, In the composite fiber substrate, the natural fiber is selected from plant natural fibers, including at least one of bamboo fiber, hemp fiber, cotton fiber, and wood pulp fiber; the average length of the natural fiber is 1.5~3.5mm, and the average aspect ratio is >50; The polymer binder is selected from at least one of waterborne acrylic resin, waterborne polyurethane resin, waterborne polyvinyl alcohol, carboxymethyl cellulose, and chitosan.
3. The protective sheet according to claim 1, characterized in that, In the composite fiber substrate, the porous inorganic material is selected from at least one of mesoporous silica, zeolite molecular sieve, and magnesia. The magnetically responsive material comprises a magnetic inorganic core and a polymer shell coating the surface of the magnetic inorganic core, wherein the mass ratio of the magnetic inorganic core to the polymer shell is 1:0.2~0.
6. The material of the magnetic inorganic core is selected from at least one of iron(II,III) oxide, γ-ferric oxide, manganese ferrite, and nickel ferrite. The polymer shell is a biodegradable polymer selected from at least one of polylactic acid and chitosan; the thickness of the polymer shell is 5~50 nm.
4. The protective sheet according to claim 1, characterized in that, The composite fiber substrate also includes 1% to 3% of the total mass of the composite fiber substrate, which are bio-based elastic fibers with shape memory effect; the bio-based elastic fibers are selected from at least one of polycaprolactone fibers and bio-based polyurethane fibers.
5. The protective sheet according to claim 1, characterized in that, In the protective sheet, the biomimetic micro-nano composite structure is composed of micron-scale fiber protrusions and nano-scale filament networks interwoven together; The surface of the biomimetic micro-nano composite structure is also loaded with an oleophilic and hydrophobic coating, the material of which is selected from at least one of modified cellulose derivatives and rosin derivatives; One surface of the protective sheet is formed with a biomimetic micro-nano composite structure; the other surface is provided with an information carrying surface for carrying customized graphic and textual information about the operation of electronic devices.
6. A method for preparing the protective sheet according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1: A mixture is prepared by mixing natural fibers, polymer binders, porous inorganic materials and magnetically responsive materials according to mass percentages; S2: The mixture is molded and dried to obtain a composite fiber substrate; S3: At least one surface of the composite fiber substrate is etched to form a biomimetic micro-nano composite structure on the surface, thereby obtaining the protective sheet.
7. The preparation method according to claim 6, characterized in that, Step S1 involves mixing natural fibers, polymer binders, porous inorganic materials, magnetically responsive materials, and bio-based elastic fibers with shape memory effect by mass percentage to obtain a mixture.
8. The preparation method according to claim 6, characterized in that, In step S2, the molding method adopts wet molding; the molding and drying specifically include the following steps: dehydrating and molding the mixture under a vacuum of -0.06~-0.04MPa to obtain a quantity of 60~70g / m³. 2 The wet paper pages; The wet paper sheet is pressed by press rollers and then subjected to gradient drying treatment to obtain the composite fiber substrate; The gradient drying process includes: drying at 75~85℃ for 1.5~2.5 min sequentially; and drying at 100~110℃ for 2.5~3.5 min. Dry at 85~95℃ for 2.0~2.5 min.
9. The preparation method according to claim 6, characterized in that, In step S3, the etching process includes any one of plasma etching and bio-enzymatic etching; Step S3, after forming the biomimetic micro-nano composite structure, further includes: loading an oleophilic and hydrophobic coating onto the surface of the biomimetic micro-nano composite structure, wherein the loading method is selected from either immersion or spraying, and the drying temperature after loading is 60~70℃. Step S3: After forming the biomimetic micro-nano composite structure on one surface of the composite fiber substrate, an information carrying surface is set on the other surface of the composite fiber substrate. The method for setting the information carrying surface includes: coating a transparent pre-coating liquid on the other surface of the composite fiber substrate, drying it at 60~80℃ to form a printing base surface, and printing water-based ink on the surface of the printing base surface to form customized graphic information.
10. The application of the protective sheet according to any one of claims 1 to 5 in surface protection of any one of the external keyboards of laptops, desktop computers, and tablet keyboards.